(untitled) (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVE: to assess the identification of health disorders as self-reported by apprentices of welding and to analyze the strength of the relationship between age and time of experience with self-reported health disorders before and after a socio-environmental nursing intervention. METHOD: this quasi-experimental, non-randomized, before-and-after study was conducted with 86 welding apprentices from a private entity. RESULTS: the results show a significant difference for the pre- and post-test means and an increase in the post-test mean score for the cardiovascular, respiratory and cutaneous systems. There was also a negative correlation between the apprentices' ages and the identification of health disorders. CONCLUSION: the socio-environmental nursing intervention enabled obtaining information on health disorders related to welding. In turn, such information enabled the apprentices to assess information and self-report health disorders.